Comparison between manual scaling and Autoscala automatic scaling applied to Sodankylä Geophysical Observatory ionograms - C.-F. Enell (Geoscientific Instrumentation, Methods and Data Systems, 2016)
This paper presents a comparison between standard ionospheric parameters manually and automatically scaled from ionograms recorded at the high-latitude Sodankylä Geophysical Observatory (SGO, ionosonde SO166, 64.1° geomagnetic latitude), located in the vicinity of the auroral oval. The study is based on 2610 ionograms recorded during the period June–December 2013. The automatic scaling was made by means of the Autoscala software. A few typical examples are shown to outline the method, and statistics are presented regarding the differences between manually and automatically scaled values of F2, F1, E and sporadic E (Es) layer parameters. We draw the conclusions that: 1. The F2 parameters scaled by Autoscala, foF2 and M(3000)F2, are reliable. 2. F1 is identified by Autoscala in significantly fewer cases (about 50  %) than in the manual routine, but if identified the values of foF1 are reliable. 3. Autoscala frequently (30  % of the cases) detects an E layer when the manual scaling process does not. When identified by both methods, the Autoscala E-layer parameters are close to those manually scaled, foE agreeing to within 0.4  MHz. 4. Es and parameters of Es identified by Autoscala are in many cases different from those of the manual scaling. Scaling of Es at auroral latitudes is often a difficult task.